The effect of the location of chickens within an open barn on productivity indicators - حسواني, نبيل (Latakia University Journal -Biological Sciences Series, 2023)
35 Ballade chicks were used in the implementation of the research, which were individually inhabited in cages in a barn of the open model. The cages are away from the barn wall towards the east, a distance of one and a half meters, while the cages are on the opposite side from the opposite wall to the west of three meters. The results indicate that the productive indicators of chickens were not affected by their location within the cages east or west of the barn. The age of sexual maturity of the chickens located west of the barn was not affected despite the delay in sexual maturity by 2 days compared to the chickens located east of the barn (not significant), Also, the average daily production of eggs was not affected, although the hens located west of the barn showed during the egg production period from 23 to 38 weeks a decrease in the average daily production of eggs by 0.04 eggs per day per hen (not significant). The average egg weight was not affected, as it decreased by 0.10 g compared to the hens located east of the barn (not significant). The feed consumption of hens west of the barn was not affected, as it decreased by 2 g/day (not significant). The amount of feed consumed to produce a kilogram of eggs decreased by 30 g compared to the hens located east of the barn (not significant). Also, the mass of eggs resulting from birds located west of the barn was not affected, as it decreased by 60 g compared with chickens located east of the barn (not significant). Likewise, the percentage of pecked eggs was not affected by the hen's claw, although the Percentage of eggs perforated through the hen's fingernail increased by 0.353% in the chickens located west of the barn (not significant). The amount of feed consumed to produce a kilogram of eggs decreased by 30 g compared to the hens located east of the barn (not significant). Also, the mass of eggs resulting from birds located west of the barn was not affected, as it decreased by 10 g compared with chickens located east of the barn (not significant). Likewise, the percentage of pecked eggs was not affected by the hen's claw, although the Percentage of eggs perforated through the hen's fingernail increased by 0.353% in the chickens located west of the barn (not significant).